Ovarian Hemangioma: a rare entity - Dahal, Mona; Upadhyaya, Paricha; Adhikari, Purbesh; Karki, Diksha; Regmi, Niraj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Ovarian hemangiomas are uncommon benign vascular tumors of ovary. Most of them are asymptomatic and detected incidentally during surgery. Authors report a case of 41 years female, parity 2; with complain of lower abdominal pain for 6 months. Ultrasonography showed a cystic lesion at right adnexa with a heterogeneously echogenic component within and devoid of internal vascularity. Laparoscopic right adnexal cystectomy was done, which on histopathological examination demonstrated features of cavernous hemangioma replacing the ovarian parenchyma. As surgical excision is treatment of choice, correct diagnosis is essential to avoid unnecessary radical surgery and treatment.